(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, the main focus is on the development of proposals and recommendations based on scientific and theoretical views on the financing of investment activities by commercial banks. Mechanisms and strategies used by banks to support investment activities were studied and an analytical perspective on their effectiveness was proposed. The article explores the various strategies and methods used by investment banks to secure capital for various projects. The importance of investment banks in the financial ecosystem is highlighted by helping to finance large projects, including infrastructure, industrial, technological and other important initiatives. Investment banks are also considered structured financing methods to create complex financial products tailored to specific project needs.